2014
DOI: 10.1038/jcbfm.2014.2
|View full text |Cite
|
Sign up to set email alerts
|

A Rat Model of Photothrombotic Capsular Infarct with a Marked Motor Deficit: A Behavioral, Histologic, and microPET Study

Abstract: We present a new method for inducing a circumscribed subcortical capsular infarct (SCI), which imposes a persistent motor impairment in rats. Photothrombotic destruction of the internal capsule (IC) was conducted in Sprague Dawley rats (male; n ¼ 38). The motor performance of all animals was assessed using forelimb placing, forelimb use asymmetry, and the single pellet reaching test. On the basis of the degree of motor recovery, rats were subdivided into either the poor recovery group (PRG) or the moderate rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
61
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 32 publications
(61 citation statements)
references
References 37 publications
0
61
0
Order By: Relevance
“…Also, the internal capsule of a rat has irregular and narrow shape, making it difficult not only to access it stereotactically but also to control the extent of infarct. 2,7 Capsular infarct leads to different clinical features and recovery patterns depending on the size and location of infarct within the internal capsule. It was assumed that motor deficit after infarct of internal capsule has good prognosis.…”
Section: Introductionmentioning
confidence: 99%
“…Also, the internal capsule of a rat has irregular and narrow shape, making it difficult not only to access it stereotactically but also to control the extent of infarct. 2,7 Capsular infarct leads to different clinical features and recovery patterns depending on the size and location of infarct within the internal capsule. It was assumed that motor deficit after infarct of internal capsule has good prognosis.…”
Section: Introductionmentioning
confidence: 99%
“…Photothrombosis has recently been used to target the internal capsule causing motor deficits lasting at least 3 weeks. 27 However, sensory function was not examined in this study, and lesions also involved the entopeduncular nucleus (corresponding to the human globus pallidus internus) that may lead to motor deficits and were adjacent to the optic tract that may cause vision defects. Moreover, mechanisms of photothrombotic injury may involve more than just tissue ischemia.…”
Section: Discussionmentioning
confidence: 93%
“…Finally, the absence of injury in other motor areas of the brain (e.g., cortex, striatum, and substantia nigra), as well as areas that may confound behavioral tests (e.g., optic nerve and tract, hippocampus), is an advantage over other models that result in white-matter injury, such as chronic forebrain hypoperfusion, chronic hypertension, intracarotid sodium laurate injection, or capsular photothrombotic lesion. 9,27,[32][33][34][35][36] Of course, ET-1 model has limitations. The mechanism of ischemia does not mimic lacunar pathophysiology, multiple vessels constrict at the same time, the duration of ischemia cannot be precisely controlled, and ET-1 targets not only endothelial and smooth muscle cells but also neurons and glia as a possible confounder.…”
Section: Discussionmentioning
confidence: 99%
“…Previously, we demonstrated that circumscribed SCI induced the depression of resting-state brain activity in bilateral cortices and striatum, and this observation was compatible with 'functional diaschisis' likely related to the neurological deficits. 18,19 Given that motor recovery was much better in the WSG than in the SSG, it is plausible that the extent of stimulation influenced both the degree and the speed of diaschisis reversal, leading to the difference in motor recovery. The microPET images support this result by showing wider activation of sensorimotor cortex and subcortical structures in the WSG than in the SSG.…”
Section: Discussionmentioning
confidence: 99%